Implementación de un sistema de detección de ataques de denegación de servicios en dispositivos IOT para hogar, utilizando herramientas open source - Agualsaca Paca, Elvis Ismael (2026)
This study presents the implementation of a denial-of-service (DoS) attack detection system in IoT devices for home environments, using open-source tools, given that the continuous development of practical, low-cost solutions for detection is essential to ensuring the security and resilience of home networks. This will be developed by studying the different types of attacks on IoT devices and how to address them, to implement a functional prototype that detects vulnerabilities. The methodology applied will be mixed, using three types of research: applied, descriptive, and exploratory, to cover different areas. It is also quasi-experimental, conducted in a controlled environment within a home laboratory. The work presents a mixed approach, mostly quantitative, whose implementation will be the final step after the documentation analysis and prototype design phases. Once implementation is complete, the Controlled Testing Phase will be executed, during which different types of DoS attacks will be sent to verify their correct detection. To conclude the research, the effectiveness of the system is measured using basic statistical tests, such as the mean, mode, median, histograms, and a dispersion matrix. Pearson correlation matrix, supplemented by a multiple regression model that partially complies with the fundamental statistical assumptions.